Effect of pH and medium composition on chain elongation with Megasphaera hexanoica producing C4-C8 fatty acids - Fernández-Blanco, Carla; Veiga, María C.; Kennes, Christian (Frontiers in Microbiology, 2023)
Chain elongation technology, which involves fermentation with anaerobic bacteria, has gained attention for converting short and medium chain substrates into valuable and longer-chain products like medium chain fatty acids (MCFAs). In the recent past, the focus of studies with pure chain elongating cultures was on species of other genus, mainly Clostridium kluyveri. Recently, other chain elongators have been isolated that deserve further research, such as Megasphaera hexanoica. This study investigates M. hexanoica's MCFA production using lactate and acetate, which served as electron donor and electron acceptor, respectively. Batch bottle studies revealed the yeast extract (YE) containing medium as the most promising in terms of production/cost ratio, producing n-caproate rapidly up to 2.62±0.24 g/L. Subsequent bioreactor experiments at pH 5.8, 6.5, and 7.2 confirmed consistent production profiles, yielding C4-C8 MCFAs. A fourth bioreactor experiment at pH 6.5 and doubling both lactate and acetate concentrations enhanced MCFA production, resulting in 3.7 g/L n-caproate and 1.5 g/L n-caprylate. H2 and CO2 production was observed in all fermentations, being especially high under the increased substrate conditions. Overall, this study provides insights into M. hexanoica's behavior in lactate-based chain elongation and highlights optimization potential for improved productivity.